Predictors of posttraumatic stress symptoms and perceived health after an acute coronary syndrome: the role of experiential avoidance, anxiety sensitivity, and depressive symptoms. Issue 12 (1st December 2020) - García-Encinas, Angélica; Ramírez-Maestre, Carmen; Esteve, Rosa; López-Martínez, Alicia E.
Abstract: Objectives: The identification of psychological markers of the posttraumatic stress reaction after a cardiac event is relevant in the management of cardiovascular risk factors. The aim of the study to test the contribution of experiential avoidance, anxiety sensitivity, and depressive symptoms to acute coronary syndrome posttraumatic stress symptoms and perceived health (both measured 6 months later), and to determine whether the associations between experiential avoidance, anxiety sensitivity, and depressive symptoms with perceived health were mediated by the posttraumatic stress symptoms. Design: 180 patients with acute coronary syndrome completed a survey over a 6-month period. Results: Anxiety sensitivity and depressive symptoms but not experiential avoidance contributed significantly to posttraumatic stress symptoms. Depressive symptoms and posttraumatic symptoms but neither anxiety sensitivity nor experiential avoidance had a significant association on perceived health. Acute coronary syndrome posttraumatic symptoms significantly mediated the association of depressive symptoms with perceived health. That is, increased depressive symptoms was significantly associated with higher levels of posttraumatic symptoms, which in turn predicted lower levels of perceived health. Conclusions: Understanding the psychological factors that are associated with post-acute coronary syndrome posttraumatic stress symptoms may help to identify patients at risk in order to refer them to the appropriate psychological care service.